YIELD OF A PORTABLE SAWMILL AND WOOD DRYING OF Hovenia dulcis IN CONVENTIONAL KILN - Marchesan, Raquel; Loiola, Pedro Lício; França, Morgana Cristina; Francisco Juízo, Claudio Gumane; Pereira da Rocha, Márcio; Klitzke, Ricardo Jorge (Floresta, 2018)
The objective of this work was to evaluate the yield of sawn wood and the operational efficiency in the sawing of Hovenia dulcis logs in a portable sawmill, as well as to evaluate the behavior of the wood in conventional kiln drying. For this purpose, five trees were selected, from which 14 logs of 1.8 meters in length were obtained to determine the volume, the yield of two diametric classes (20 to 24 and 24.1 to 28 cm) and the operational efficiency during the sawing of the logs. For the drying process, the parameters of initial temperature, final temperature and drying potential were obtained from the drastic drying method at 100ºC. The yield results showed that there were no statistical differences between the two diametric grades. For operational efficiency, the highest diameter class (1.00m³/worker/day) was higher than the lower diameter class (0.70m²/worker/day). For the drying of Hovenia dulcis wood, it is possible to consider this species as a difficult drying type according to the parameters found for the elaboration of the drying programs. In addition, the moisture loss of the wood occurred slowly due to its low permeability.